2016
DOI: 10.7567/jjap.55.10tb09
|View full text |Cite
|
Sign up to set email alerts
|

Electrocaloric properties of potassium tantalate niobate crystals

Abstract: The electrocaloric properties of potassium tantalate niobate (KTN) crystals were investigated by indirect estimation and direct measurement of temperature–electric field (T–E) hysteresis loops. The measured T–E loops showed a similar shape to strain–electric field (s–E) loops. The adiabatic temperature change ΔT due to the electrocaloric effect was estimated from the polarization change of this sample to be 0.49 K under a field of 20 kV/cm. The measured temperature change ΔT in these samples upon the release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The parameter ξ is also utilized to evaluate the performance of different materials under the unit of electric field. The ξ of the ceramic with x = 0.01 approaches 0.3 K·mm/kV, which is competitive with the ECE efficiency of the other relaxor ferroelectric ceramics, as shown in Table . With respect to the ECE, aside from the polarization contribution, the diffuse phase transition and the existence of PNRs also play an important role in the temperature stability of the ECE.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The parameter ξ is also utilized to evaluate the performance of different materials under the unit of electric field. The ξ of the ceramic with x = 0.01 approaches 0.3 K·mm/kV, which is competitive with the ECE efficiency of the other relaxor ferroelectric ceramics, as shown in Table . With respect to the ECE, aside from the polarization contribution, the diffuse phase transition and the existence of PNRs also play an important role in the temperature stability of the ECE.…”
Section: Resultsmentioning
confidence: 88%
“…The ξ of the ceramic with x = 0.01 approaches 0.3 KÁmm/kV, which is competitive with the ECE efficiency of the other relaxor ferroelectric ceramics, as shown in Table 1. [48][49][50][51][52][53] With respect to the ECE, aside from the polarization contribution, the diffuse phase transition and the existence of PNRs also play an important role in the temperature stability of the ECE. The alignment of the PNRs will be easily induced by the external electric field, which is beneficial for the enhancement of the ECE.…”
Section: Directly Measured Electrocaloric Effect Of the Bkt-xlmt Cementioning
confidence: 99%
“…The dP/dT between 10 °C and 80 °C and estimated ¨T from Equation (1) for these ceramics are shown in Table 1. [18] Among these samples, it is estimated that the PZT ceramics with Tc of 140 C exhibited largest ΔT. [19] Considering that both ECE and field-induced displacement derive from the change in polarization, the similar appearance of the loops is reasonable.…”
Section: Methodsmentioning
confidence: 99%
“…A‐site doped with Li in KTN represents anti‐diffracting, which is attributed to both A‐site and B‐site ion‐disordered, and the coupling among them in KTN:Li . Recently, Maiwa reported that KTN:Li shows a large EC strength of Δ T = 0.42 K under E = 20 kV cm −1 near room temperature. But Li doping can obviously reduce the Nb content to remain the T c near room temperature, and induce distinctly different kind of polarization behavior …”
Section: Comparison Of the Ece Properties In Bulk Materials In The Mmentioning
confidence: 99%